Effects of Aqueous and Alcoholic Extracts of Peganum harmala L. Seeds on Male Fertility of White Mice Treated with Olanzapin Drug - Hind A. Hanon (Journal of Global Pharma Technology, 2018)
This study was designed to study the effects of aqueous and alcoholic extracts of Peganum harmala L. Seeds on male fertility of white mice treated with Olanzapin, males were 25 to 30 days old and had a mean weight of 35 g. The mice were divided into two groups, a total of 5 negative control males were injected with distilled water for 15 days, the positive control group (experimental group) injected with Olanzapin drug for 15 days, the was then divided into five subgroups, the first subgroup consists of 5 males were injected with the drug only, while the other four subgroups were dosed with aqueous and alcoholic extracts for 7 days. The first subgroup dosage was with low concentration of aqueous extract (12 mg / kg) and the second with a high concentration of the aqueous extract at a concentration of 24 mg / kg, the third subgroup was dosage with the low concentration of the alcoholic extract at 12 mg / kg and the fourth was dosage with a high concentration of the alcoholic extract at a concentration of 24 mg / kg. The results showed a significant increase (p <0.01) in the level of prolactin hormone in the positive control mice serum, compared to the control group as well as a significant decrease in the level of testosterone hormone as well as the characteristics of the epididymal sperms represented by sperm concentration and percentages of normal and moving sperm. The dosage with aqueous and alcoholic extracts of the Peganum harmala led to the occurrence of significantly higher concentration (p <0.01) of the testosterone hormone and significantly lower in the level of the prolactin hormone concentration when compared with the experimental group as well as a significant improvement of p <0.01) in the parameters of epididymal sperms, and the best concentration was for the aqueous plant extract which 12 mg / kg.Keywords: Olanzapin, Piganum harmala, Testosterone, Prolactin, Sperms.